Expression of CD40 and CD192 in Classical Monocytes in Multiple Sclerosis Patients Assessed with Transcranial Magnetic Stimulation - Nikolina Režić Mužinić; Anita Markotić; Sanda Pavelin; Denis Polančec; Maja Buljubašić Šoda; Antonia Bralić; Joško Šoda; Angela Mastelić; Una Mikac; Ana Jerković; Maja Rogić Vidaković (Biomedicines, 2023)
Expression of CD40 and CD192 markers in different monocyte subpopulations has been reported to be altered in people with MS (pwMS). Also, functional connectivity of the corticospinal motor system pathway alterations has been proved by transcranial magnetic stimulation (TMS). The study objective was to investigate the expression of CD40 and CD192 in classical (CD14++CD16−), intermediate CD14++CD16+ and non-classical (CD14+CD16++) blood monocyte subpopulations in pwMS, undergoing neurophysiological TMS assessment of the corticospinal tract integrity by recording motor-evoked potentials (MEPs). Radiological examination on lesion detection with MRI was performed for 23 patients with relapsing–remitting MS treated with teriflunomide. Then, immunological analysis was conducted on peripheral blood samples collected from the patients and 10 healthy controls (HC). The blood samples were incubated with anti-human CD14, CD16, CD40 and CD192 antibodies. Next, pwMS underwent neurological testing of functional disability (EDSS) and TMS assessment with recording MEPs from upper and lower extremity muscles. The results show that in comparison to HC subjects, both pwMS with normal and altered MEP findings (prolonged MEP latency or absent MEP response) had significantly decreased surface receptor expression measured (MFIs) of CD192 and increased CD40 MFI in classical monocytes, and significantly increased percentages of classical and total monocytes positive for CD40. Knowing CD40’s pro-inflammatory action, and CD192 as a molecule that enables the passing of monocytes into the brain, decreased CD192 in classical monocytes could represent a beneficial anti-inflammatory parameter.